Improving T-Kick Accuracy Through Chair and Peching Box Training in Pencak Silat Athletes from Naga Pertapa Indonesia, Padepokan Muara Muntai - Nabila Silva Husna; Naheria; Gyta Krisdiana Cahyaningrum; Muhammad Rifai (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2026)
This study aims to improve the accuracy of T kicks using chairs and peching boxes on the accuracy of T kicks by athletes from the Indonesian Pencak Silat Naga Pertapa Padepokan Muara Muntai. The study used a quantitative approach with a one-group pretest-posttest design. The sample consisted of 14 athletes selected using purposive sampling. The research instrument was a kicking accuracy test. The treatment was given during 12 sessions with a frequency of three times a week. Data analysis included descriptive statistics, Shapiro-Wilk normality test, and Paired Sample T-Test. The results showed that the pretest average of 5.43 increased to 10.64 in the posttest. The normality test stated that the data was normally distributed (Sig. 0.249 and 0.252 > 0.05). The hypothesis test obtained a Sig. value of 0.000 < 0.05, which means that there was a significant increase after the treatment. Training with assistive media proved to be able to improve accuracy, direction control, and accuracy of T kicks through more directed movement repetition. The use of chairs and peching boxes was effective in improving the accuracy of T kicks by pencak silat athletes and can be used as an alternative in the preparation of training programs.